1992
DOI: 10.1007/bf02207955
|View full text |Cite
|
Sign up to set email alerts
|

The role of pregnancy in the course and aetiology of rheumatoid arthritis

Abstract: The aetiology of rheumatoid arthritis (RA) is unknown, although being female is generally recognized as the most important independent risk factor, the disease being 2 to 3 times more frequent in females than in males. The dramatic effect of pregnancy in rheumatoid arthritis has been documented for over 50 years. This review examines the evidence and possible mechanisms by which pregnancy modifies the disease process and may alter predisposition to the development of RA in later life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
4

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(82 citation statements)
references
References 52 publications
2
76
0
4
Order By: Relevance
“…A number of disease-modifying agents (methotrexate and gold) promote Th2 cells while suppressing Th1 cells [33,34]. In addition, many women experience improvement of their arthritis during pregnancy (reviewed in [35]), and the switch towards a Th2 profile in pregnancy may be at least partially responsible [36]. Synovial fluid from patients with RA has shown either low or absent IL-4 [37], although Raza et al demonstrated a distinct cytokine profile in synovial fluid (SF) which included IL-4 [2].…”
Section: Discussionmentioning
confidence: 99%
“…A number of disease-modifying agents (methotrexate and gold) promote Th2 cells while suppressing Th1 cells [33,34]. In addition, many women experience improvement of their arthritis during pregnancy (reviewed in [35]), and the switch towards a Th2 profile in pregnancy may be at least partially responsible [36]. Synovial fluid from patients with RA has shown either low or absent IL-4 [37], although Raza et al demonstrated a distinct cytokine profile in synovial fluid (SF) which included IL-4 [2].…”
Section: Discussionmentioning
confidence: 99%
“…While the etiology of MS is unknown, a Th1-mediated autoimmune component driven by myelin protein-specific, proinflammatory cytokine-secreting T lymphocytes is believed to be involved in the pathogenesis. A beneficial effect of pregnancy on clinical symptoms has been observed in MS and other Th1-mediated autoimmune diseases, including rheumatoid arthritis (RA), psoriasis, uveitis, and thyroiditis (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Interestingly, most of these diseases are characterized by temporary rebound exacerbations postpartum (2, 4, 5, 7-9, 14, 17, 20).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…Iron deficiency anemia is also one of the most frequently encountered complications of pregnancy. Daily iron requirement increases tenfold during pregnancy (5). This is mainly due to iron transferred to the fetus and placenta, cord iron, and iron in postpartum bleeding (6).…”
Section: Influence Of Pregnancy On Rheumatoid Arthritismentioning
confidence: 99%